Staphylococcus aureus Putative Vaccines Based on the Virulence Factors: A Mini-Review - Mirzaei, Bahman; Babaei, Ryhaneh; Zeighami, Habib; Dadar, Maryam; Soltani, Ali (Frontiers in Microbiology, 2021)
Since the 1960s, the frequency of Methicillin-resistant Staphylococcus aureus as a recurrent cause of nosocomial infections has increased. Since MDR Staphylococcus has overcome antimicrobial treatment, the development of putative vaccines based on virulence factors could be a great help in controlling the infections caused by bacteria and are actively being pursued in healthcare settings. This mini-review provides an overview of the recent progress in vaccine development, immunogenicity, and therapeutic features of some S. aureus macromolecules as putative vaccine candidates and their implications against human S. aureus-related infections. Based on the reviewed experiments, multivalent vaccines could prevent the promotion of the diseases caused by this bacterium and enhance the prevention chance of S. aureus infections.